The validity of resting metabolic rate (RMR)-prediction equations and reliability of measured RMR in female athletes - Mackay, K.; Schofield, K.; Sims, S.; McQuillan, J.; Driller, M. (International Journal of Exercise Science, 2019)
The aim of the current study was to; 1) assess the test-retest reliability of an indirect calorimetry analyzer (Parvo Medics TrueOne), and 2) compare measured RMR with three RMR-predictive (pRMR) equations in female athletes. In part one, 12 recreationally-exercising women (mean ± SD; age 27.5 ± 12.3 y) performed two RMR assessments, on separate days, utilising the Parvo Medics TrueOne analyser. In part two, 25 recreationally-exercising women to sub-elite athletes (mean ± SD; age 30.1 ± 10.2 y) underwent an RMR assessment using the Parvo Medics TrueOne analyser, which was compared to three calculated pRMR equations (Harris-Benedict (H-B) , Mifflin-St Jeor (M), World Health Organisation (WHO)). eTest-retest reliability for the TrueOne analyser was deemed acceptable (CV = 5.3%, ICC = 0.92). The validity of pRMR when compared to measured RMR showed low levels of agreement in all 3 predictive equations (M: CV = 21.4%, TEE = 269 kcal.day-1, r = 0.16, WHO: CV = 21.5%, TEE = 270 kcal.day-1, r = 0.13 H-B: CV = 21.6%, TEE = 270 kcal.day-1, r = 0.13). The Parvo Medics TrueOne analyser is a reliable tool for measuring RMR. Caution should be taken when using pRMR equations in female athletes as they do not take into account the likely differences in fat free mass in these populations.